Zimbabwe's Exodus : Crisis, Migration, Survival. - Crush, Jonathan (Institute for Democracy in South Africa, 2010)
The ongoing crisis in Zimbabwe has led to an unprecedented exodus of over a million desperate people from all strata of Zimbabwean society. The Zimbabwean diaspora is now truly global in extent. Yet rather than turning their backs on Zimbabwe, most maintain very close links with the country, returning often and remitting billions of dollars each year. Zimbabwe's Exodus. Crisis, Migration, Survival is written by leading migration scholars many from the Zimbabwean diaspora. The book explores the relationship between Zimbabwe's economic and political crisis and migration as a survival strategy. T.